Protective Effects of Melatonin and Mitochondria-targeted Antioxidants Against Oxidative Stress: A Review - R. Ramis, M.; Esteban, S.; Miralles, A.; Tan, Dun-Xian; J. Reiter, R. (Current Medicinal Chemistry, 2015)
Oxidative damage is related to aging and a wide range of human disorders. Mitochondria are in large part responsible for free radical production and they are also main targets of the attack of these toxic molecules. The resulting deleterious effects of the damage to mitochondria can be prevented by antioxidants. Melatonin is an endogenouslyproduced indoleamine that modulates numerous functions, including mitochondria-related functions; this result from its capacity to penetrate all morphophysiological barriers and to enter all subcellular compartments due to its amphiphilic nature. Furthermore, this indoleamine and its metabolites are powerful antioxidants and scavengers of free radicals, protecting cellular membranes, the electron transport chain and mitochondrial DNA from oxidative damage. These properties may make melatonin a potent protector against a variety of free radical-related diseases. By comparison, other conventional antioxidants have less efficacy due to their limited access to the mitochondria. In recent years, research has focused on the advancement of mitochondria-targeted antioxidants, such as MitoQ (composed by the lipophilic triphenylphosphonium cation conjugated to the endogenous antioxidant coenzyme Q10) and MitoE (composed by the triphenylphosphonium cation attached to the antioxidant α-tocopherol). Mitochondria-targeted antioxidants accumulate in several hundred-fold greater concentrations within mitochondria and protect these critical organelles from oxidative damage. Melatonin also seems to be a mitochondria-targeted antioxidant and has similar protective actions as the synthetic antioxidants. Further work is required to determine the therapeutic properties of these antioxidants in ameliorating diseases related to mitochondrial dysfunction.
Keywords: mitoQ